Fire regimes and variability in aboveground woody biomass in miombo woodland. Issue 5 (31st May 2014) - Saito, Makoto; Luyssaert, Sebastiaan; Poulter, Ben; Williams, Mathew; Ciais, Philippe; Bellassen, Valentin; Ryan, Casey M.; Yue, Chao; Cadule, Patricia; Peylin, Philippe
Abstract This study combined a process‐based ecosystem model with a fire regime model to understand the effect of changes in fire regime and climate pattern on woody plants of miombo woodland in African savanna. Miombo woodland covers wide areas in Africa and is subject to frequent anthropogenic fires. The model was developed based on observations of tree topkill rates in individual tree size classes for fire intensity and resprouting. Using current and near‐future climate patterns, the model simulated the dynamics of miombo woodland for various fire return intervals and grass cover fractions, allowing fire intensity to be estimated. There was a significant relationship between aboveground woody biomass and long‐term fire regimes. An abrupt increase in fire intensity and/or fire frequency applied as a model forcing led to reduced long‐term average aboveground woody biomass and mean tree size. Fire intensity increased with increasing living grass biomass (which provides increased flammable fuel), thereby affecting the relationship between fire regime and tree size, creating a demographic bottleneck on the route to tree maturity. For the current fire regime in miombo woodland, with a fire return interval of about 1.6–3 years, the model‐predicted fire intensity lower than 930–1700 kW m−1 is necessary to maintain today's aboveground woody biomass under current climate conditions. Future climate change was predicted to have a significant positive effect on woody plants in miombo woodland associated with elevated CO2 concentration and warming, allowing woody plants to survive more effectively against periodic fires.